2012
DOI: 10.1002/jcu.22018
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonography for preoperative assessment of deep endometriosis

Abstract: TVS appears to be useful for the detection of endometriosis located in the bladder and involving the sigmoid colon, the rectovaginal septum, and the rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 29 publications
(35 reference statements)
5
42
2
1
Order By: Relevance
“…The rectum, sigmoid, and rectovaginal septum are often considered together, and the Douglas obliteration was described as an indirect sign of DIE (26). Other studies (17,20) reported a lower accuracy compared with our results, probably due to a retrospective analysis of the TVS findings (17) or to the small number of patients (20).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The rectum, sigmoid, and rectovaginal septum are often considered together, and the Douglas obliteration was described as an indirect sign of DIE (26). Other studies (17,20) reported a lower accuracy compared with our results, probably due to a retrospective analysis of the TVS findings (17) or to the small number of patients (20).…”
Section: Discussioncontrasting
confidence: 75%
“…To detect DIE extension into the pelvis, use of magnetic resonance imaging (MRI) (7)(8)(9)(10)(11)(12) and transvaginal sonography (TVS) (6,(13)(14)(15)(16)(17)(18) have been described. The MRI provides accurate information about lesions located on the upper level of the sigmoid, but for pelvic disease TVS is equally accurate and is considered the first and most widely used diagnostic tool (6,(18)(19)(20).…”
mentioning
confidence: 99%
“…The high accuracy in detecting and describing DIE lesions by transvaginal sonography is similar or better than those obtained by recent studies on magnetic resonance imaging [56,99,100]. For these reasons, it seems that transvaginal sonography is the best diagnostic tool in mapping DIE [36, [48][49][50]57,58].…”
Section: Resultsmentioning
confidence: 58%
“…Although reported sensitivity and specificity of transvaginal sonography in the prediction of DIE is high [47][48][49][50][51][52][53][54][55][56][57][58], evaluation of DIE by transvaginal sonography is difficult and requires expertise. Therefore, some easily detectable utrasonographic signs have recently been proposed to predict the risk of the presence of DIE.…”
Section: Deep Infiltrating Endometriosis Of the Posterior-lateral Commentioning
confidence: 99%
“…In the first round of literature search, out of 317 manuscripts, only 17 articles were included according to the inclusion and exclusion criteria (4,9,16,19,21,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The following rounds of literature screen to detect manuscripts regarding modified techniques of TVS identified 12 eligible manuscripts, of which three were already identified in the first literature search (4,19,21) and nine were new manuscripts (13,20,22,23,(37)(38)(39)(40)(41).…”
Section: Resultsmentioning
confidence: 99%